1997
DOI: 10.1055/s-2006-957622
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Soyasaponin II on Virus Replicationin vitro

Abstract: The antiviral activities of two saponins, soyasaponin I and II, isolated from soybean (Glycine max Merrill) were studied in vitro against herpes simplex virus type 1 (HSV-1). Soyasaponin II was more potent than soyasaponin I as shown by reduction of HSV-1 production. Soyasaponin II was also found to inhibit the replication of human cytomegalovirus, influenza virus, and human immunodeficiency virus type 1. The action was not due to inhibition of virus penetration and protein synthesis, but might involve a viruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 7 publications
1
41
0
1
Order By: Relevance
“…The antiviral activity of soyasaponin against the herpes simplex virus, human immunodeˆciency virus, human cytomegalovirus, and FluV A has been reported. [8][9][10][11] Since it has been reported that soyasaponin was recovered in 70z aqueous ethanol, we presumed that the antiviral activity of the hot-water extract of black soybean against Ad1 would have come from compound(s) other than soyasaponin. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral activity of soyasaponin against the herpes simplex virus, human immunodeˆciency virus, human cytomegalovirus, and FluV A has been reported. [8][9][10][11] Since it has been reported that soyasaponin was recovered in 70z aqueous ethanol, we presumed that the antiviral activity of the hot-water extract of black soybean against Ad1 would have come from compound(s) other than soyasaponin. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since acute respiratory tract diseases are mainly caused by infection from viruses such as the adenovirus, in‰uenza virus, and coxsackievirus, 7) we have presumed that the pharmacological eŠect of the black soybean extract on the disease might be due to antiviral activity. Concerning the antiviral activity of soybean, it has been reported that soyasaponin from the common yellowish soybean inhibited the replication of the herpes simplex virus, 8,9) human immuno-deˆciency virus (HIV), 8,10,11) cytomegalovirus, 8) and in‰uenza virus. 8) However, the speciˆc antiviral activity of the black soybean extract against respiratory illness viruses has not been previously investigated.…”
mentioning
confidence: 99%
“…Soyasaponin II (36) was also found to inhibit the replication of human cytomegalovirus and influenza virus. This action was not due to inhibition of virus penetration and protein synthesis, but may involve a virucidal effect (105). In a structure-activity relationship study, the activity of soyasapogenol A (54) was less than 1/20 of that of soyasapogenol B (55), and the hydroxylation at C-21 seemed to reduce anti-HSV-1 activity (106).…”
Section: Anti-viral Activitiesmentioning
confidence: 99%
“…In addition, they have been employed as immunological adjuvants in vaccine formulations due to their immune enhancing properties (Kensil et al 2004). For instance, saponins appear to inhibit the infectivity of the AIDS virus (Nakashima et al 1989;Vlietinck et al 1998) and the herpes simplex virus type 1 (Hayashi et al 1997). Soyasaponins are reported to be hepatoprotective (Kinjo et al 2003) and have also shown a preventive effect on the growth of human colon cancer cells (Tsai et al 2010).…”
Section: Saponinsmentioning
confidence: 99%